Are Skills Constraining Growth in Bosnia and Herzegovina? - World Bank (World Bank, 2012)
The shortage of skills sought by key export-oriented and import competing industries in Bosnia and Herzegovina (henceforth, 'BH') is substantial and if left unaddressed, threatens to constrain future economic growth of the country. Prior to the onset of the global economic crisis, BH enjoyed strong rates of economic growth based to a significant degree on the growth of exports. On average, exports grew at an impressive 34 percent per year between 1995 and 2008. Our analysis however confirms that the growth of exporting, as well as import-competing industries is increasingly becoming constrained by the shortage of skills in the labor force. In this report we seek to identify these shortages and their likely causes and recommend reforms and policies which can prevent the plummeting of economic growth due to lack of adequate skills. Firm-level evidence confirms that the shortage of qualified workers is becoming a serious obstacle to growth of BH exporting companies. This report investigates what types of skills firms are looking for and are not finding in the marketplace. The policy recommendation section of this study seeks to provide ideas and direction for the BH government to address these labor market challenges.